Pengaruh Pemberian Nanopartikel Kitosan - Ekstrak Batang J. multifida L terhadap Jumlah Eritrosit M. musculus yang Teriinfeksi P. berghei - Arsela Eko Listiono; M. Lutfi Firdaus; Agus Sundaryono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the effect of administering chitosan nanoparticles loaded with Jatropha multifida L. stem extract on the erythrocyte count of Mus musculus infected with Plasmodium berghei as well as their characterization results. The method used was the preparation of chitosan nanoparticles loaded with J. multifida L. stem extract using the ionic gelation method. Characterization results using Particle Size Analysis (PSA) showed that the chitosan nanoparticles loaded with J. multifida L. stem extract had an average particle size of 567.12 nm with a polydispersity index (PDI) value of 0.11, while characterization using X-ray diffraction (XRD) showed the highest peak at a 2θ angle of 28.68°. The results indicated differences in the effects of varying concentrations of chitosan nanoparticles loaded with J. multifida L. stem extract on erythrocyte counts. The conclusion of this study is that the most effective dose of chitosan nanoparticles loaded with J. multifida L. stem extract was 0.028 g/kg body weight, followed by the administration of crude J. multifida L. stem extract at the same dose. Keywords: Erythrocytes, Jatropha multifida L., Chitosan, Nanoparticles, Particle Size Analysis, Plasmodium berghei, X-ray Diffraction